Nationalism in a new Syria - Diogo Bercito (Malala)
This article investigates the role of the mahjar on the development of Arab nationalism, with a particular interest in Antoun Saadeh’s experience in Latin America. Like many other Arab nationalism ideologues, he developed his conception of the “nation” during the years he spent abroad. His ideas were present in Suriya al Jadida, a newspaper he published in Brazil from 1939 to 1941. I analyze three articles from that publication in order to understand how he reached out to the diaspora in Latin America and the role he expected it to play. With that, I emphasize the importance of the mahjar to the political thought of Arabic-speaking countries.